Benefits and Challenges of Bookkeeping and Accounting Practices of SMEs and Its Effect on Growth and Performance in Ghana - Alhassan Musah (STIE Malangkucecwara, 2017)
The study was to examine investigates bookkeeping and accounting practices in SMEs and the extent to which this support the operations and growth of the enterprises. In doing so, it sought to establish the kinds of bookkeeping and accounting practices SMEs kept; the extent to which bookkeeping and accounting information support the operations and growth of the SMEs and performance; the general attitude of SMEs owners towards bookkeeping and accounting practices and the challenges faced by the SMEs entrepreneurs in bookkeeping and accountingpractices. The study sampled 120 SMEs in Accra who have been operating for at least five years. Data was collected through the administration of questionnaires with the help of students from Dominion University College and analysed using descriptive statistics and Pearson correlation. The findings show that some of the SMEs owners/managers do keep subsidiarybooks of accounts. The findings showed that by accurately keeping the records they were able to take essential decision and made business adjustments accurately, they were able to have reduced operating costs and improved efficiency and productivity. The findings of the study show that the SMEs owners/managers had positive attitude towards the bookkeeping and accounting recordkeeping but lacked adequate knowledge of the recording. The findings of the study also indicate that the SMEs owners faced various challenges in their record keeping process including lack of accounting knowledge and absence of specific guidelines for bookkeeping and accounting recordkeeping, fear of discouragement in case of a loss, inadequate education and training skills, and cost and time constraints. Finally, the results showed a positive association between bookkeeping practices and SMEs growth and performance in Ghana.